2021
DOI: 10.1111/dom.14557
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial renal haemodynamic effects of the dipeptidyl peptidase‐4 inhibitor linagliptin versus the sulphonylurea glimepiride in adults with type 2 diabetes (RENALIS): A predefined substudy of a randomized, double‐blind trial

Abstract: Aim: To determine the effect of the dipeptidyl peptidase-4 inhibitor linagliptin on postprandial glomerular hyperfiltration compared with the sulphonylurea glimepiride in adults with type 2 diabetes (T2D). Materials and Methods:In this predefined substudy within a randomized, doubleblind, parallel-group, intervention trial, overweight people with T2D without renal impairment were treated with once-daily linagliptin 5 mg (N = 10) or glimepiride 1 mg (N = 13) as an add-on to metformin for 8 weeks. After a standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Another aspect of interest in this context appears to be postprandial renal hyperfiltration, which can be observed after the intake of a protein‐rich meal 37 . Since a recent study investigating the effects of linagliptin on postprandial hyperfiltration showed an increase in postprandial filtration fraction compared to glimepiride, 38 data on fasting and postprandial eGFR might have added interesting information on the effects of linagliptin on postprandial hyperfiltration. However, since the “test meal” did not contain any protein, potential effects of postprandial (hyper‐)filtration in the present study remain speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect of interest in this context appears to be postprandial renal hyperfiltration, which can be observed after the intake of a protein‐rich meal 37 . Since a recent study investigating the effects of linagliptin on postprandial hyperfiltration showed an increase in postprandial filtration fraction compared to glimepiride, 38 data on fasting and postprandial eGFR might have added interesting information on the effects of linagliptin on postprandial hyperfiltration. However, since the “test meal” did not contain any protein, potential effects of postprandial (hyper‐)filtration in the present study remain speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial glomerular hyperfiltration may be one of the renal risk factors in diabetic patients. Compared with glimepiride, linagliptin does not improve postprandial hemodynamics, and may even moderately induce postprandial glomerular hyperfiltration ( Muskiet et al, 2020 ; Muskiet et al, 2022 ).…”
Section: Cardiorenal Protection Of Sglt2i Glp-1ras and Dpp-4imentioning
confidence: 99%